Requesting and Refusing Politeness Expression Teacher’s Instruction in Teaching Learning Process - Damanik, Bernieke Anggita Ristia (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2020)
This research conducted to describe the request and refusal polite expression when teacher instruct students. The writer has chosen English teacher and the object is 1 teacher. The writer joins in the class and records the activities when teachers teach students. The data analyzed by using qualitative method. The types of politeness are based on the Brown and Levinson’s theory about politeness strategy that should people use when they instruct others. There are 24 male students and 30 female students who are follow this research. The research instrument to collect the data is through observation the conversation during learning and teaching process. All the utterances relate to politeness strategy produced by the students and teacher write down and 2 conversations are chose to be analyzed based on politeness strategies The result of this research shows that there are three types of instructional activities; motivating students (1 expression), informing students of objective (1 expression), helping students recall prerequisites (1 expression), presenting information and example (1 expression) and providing practice and feedback (7 expressions). Teacher used four types of them, Bald on Record (4 expressions), Positive Politeness (16 expressions), Negative Politeness (6 expressions), and off- record (2 expressions). There are 3 expressions are polite requests and no impolite refusal. From that result, the writer concludes that teacher often to use Positive Politeness by reasoning that it types of politeness strategy is to make the relationship between teacher and students more intimate during teaching learning process. This research can lead other researcher to conduct research on Politeness strategy. It also can lead the teachers and the students to make a good interaction by applying the politeness strategy in the classroom so that they can maintain a good communication one another